PEMODELAN DAN SIMULASI PEMANAS AIR ENERGI SURYA DENGAN KOLEKTOR PIPA PARALEL - Darmanto, Ganang; Sambada, F.A.Sambada Rusdi (ReTII, 2018)
Hot water is one of the needs in everyday life, starting from household needs such as brewing drinks to bathing. Hot water is not only needed for household needs but is also needed in the industrial world such as sterilizing materials at high temperatures, and so on. There are many ways to get the hot water, from using fossil fuels to electricity. Solar energy water heaters that are currently available are still not optimal, this is due to the lack of development guidelines in the design phase of solar energy water heaters. From these problems, many obtained the results of hot water temperatures and the efficiency of solar energy water heaters that are still not optimal. Therefore, to overcome this problem modeling and simulation efforts are needed. This is done to get a better design of a solar energy water heater. The research of solar energy water heaters aims to measure the maximum temperature of hot water that can be produced, find out the efficiency factor of solar energy water heaters and find out the comparison of simulations with solar energy water heaters. In this study the temperature of the collector, glass temperature, ambient temperature, water temperature in the collector and the temperature of the water in the storage tank will be measured. Data from the results of these studies are then calculated to look for efficiency factors of solar energy water heaters and then graphs will be made in the form of a comparison of simulations with tools. From this study, the lowest hot water temperature was 30.21 ° C and the highest hot water temperature was 49.40 ° C. And obtained the lowest efficiency factor of 92.86% and the highest efficiency factor of 96.81%. Then the results obtained that the material used in the simulation is better than the tool used. Keywords: Water Heater, Parallel Pipe Collector, Simulation